Responses of the criminal justice system - Smit, Paul (International statistics on crime and justice, 2010)
In this chapter the repsonses of the criminal justice system on crime are described, from the moment an offender is found until a decision of a judge at a penal court. The number of persons prosecuted and convicted are analysed, both adults and juveniles as well as the proportion of females. This is done for total offences and separately for intentional homicide. Where possible, data are given by country and by continent. Next, the attrition process is discussed in two ways. Firstly the number of offenders convicted are compared to the offenders found. Secondly, the attrition process is shown in more detail with four moments in the criminal justice system, i.e. crimes recorded, offenders foubnd, offenders prosecuted and offenders convicted.